Ginkgo biloba Extract (GbE) Stimulates the Hypothalamic Serotonergic System and Attenuates Obesity in Ovariectomized Rats - Renata M. Banin; Renata M. Banin; Iracema S. de Andrade; Suzete M. Cerutti; Lila M. Oyama; Mônica M. Telles; Mônica M. Telles; Eliane B. Ribeiro (Frontiers Media S.A., 2017)
Menopause is associated with increased risk to develop obesity but the mechanisms involved are not fully understood. We have shown that Ginkgo biloba extract (GbE) improved diet-induced obesity. Since GbE might be effective in the treatment of obesity related to menopause, avoiding the side effects of hormone replacement therapy, we investigated the effect of GbE on hypothalamic systems controlling energy homeostasis. Wistar rats were either ovariectomized (OVX) or Sham-operated. After 2 months, either 500 mg.kg-1 of GbE or vehicle were administered daily by gavage for 14 days. A subset of animals received an intracerebroventricular (i.c.v.) injection of serotonin (300 μg) or vehicle and food intake was measured after 12 and 24 h. Another subset was submitted to in vivo microdialysis and 5-HT levels of the medial hypothalamus were measured by high performance liquid chromatography, before and up to 2 h after the administration of 500 mg.kg-1 of GbE. Additional animals were used for quantification of 5-HT1A, 5-HT1B, 5-HT2C, 5-HTT, and pro-opiomelanocortin hypothalamic protein levels by Western blotting. OVX increased food intake and body weight and adiposity while GbE attenuated these alterations. i.c.v. serotonin significantly reduced food intake in Sham, Sham + GbE, and OVX + GbE groups while it failed to do so in the OVX group. In the OVX rats, GbE stimulated 5-HT microdialysate levels while it reduced hypothalamic 5-HTT protein levels. The results indicate that GbE improved the ovariectomy-induced resistance to serotonin hypophagia, at least in part through stimulation of the hypothalamic serotonergic activity. Since body weight gain is one of the most important consequences of menopause, the stimulation of the serotonergic transmission by GbE may represent a potential alternative therapy for menopause-related obesity.